Insured persons dilemma about other family members: a perspective on the national health insurance scheme in Nigeria - Nasir Umar; Shafiu Mohammed (AOSIS, 2011)
The need for health care reforms and alternative financing mechanism in many low and middle-income countries has been advocated. This led to the introduction of the national health insurance scheme (NHIS) in Nigeria, at first with the enrollment of formal sector employees. A qualitative study was conducted to assess enrollee's perception on the quality of health care before and after enrollment. Initial results revealed that respondents (heads of households) have generally viewed the NHIS favorably, but consistently expressed dissatisfaction over the terms of coverage. Specifically, because the NHIS enrollment covers only the primary insured person, their spouse and only up to four biological children (child defined as <18 years of age), in a setting where extended family is common. Dissatisfaction of enrollees could affect their willingness to participate in the insurance scheme, which may potentially affect the success and future extension of the scheme.